Qualidade do leite e efeito do processamento sobre a segurança microbiológica do Queijo Porungo - Cardoso, Maria Luiza (Universidade Federal de São Carlos, 2024)
Porungo is a traditional artisanal cheese produced in the southwestern region of São Paulo state. Although the milk used in its production is not thermally treated, which could pose a risk of pathogen contamination, the curd undergoes a hot water stretching process. This study aimed to evaluate the quality of the raw milk used in the production of Porungo cheese, as well as the impact of processing on the contaminating microbiota. Milk samples were collected from seven cows at a Porungo cheese production unit and analyzed for somatic cell count (SCC), standard plate count (SPC), total coliforms, Escherichia coli, enterobacteria, molds and yeasts, Staphylococcus aureus, and Streptococcus spp., as well as chemical composition. Over the course of a year, samples of milk, fermented-whey, curd, cheese post-stretching, and cheese post-salting were collected and evaluated for aerobic mesophilic bacteria, total and thermotolerant coliforms, and S. aureus counts. Additionally, the effect of stretching in hot water at temperatures between 65 and 72 °C on the viability of Listeria innocua inoculated into the Porungo cheese curd was evaluated. Three of the seven cows evaluated had SCC levels above 400,000 SC/mL, with S. aureus detected at levels exceeding 3 log CFU/mL in all milk samples, indicating the presence of subclinical mastitis in some animals. All raw milk samples freshly collected had SPC levels below 4.5 log CFU/mL, while fat and total solids content were extremely low. Aerobic mesophilic bacteria and S. aureus counts were not influenced by the season but showed significant differences among the cheese processing stages. Although the stretching stage did not significantly reduce the microbial population in both groups evaluated, a significant reduction was observed in the cheese after salting. The total coliform population varied throughout the evaluation period and among the stages analyzed, with no samples showing contamination by thermotolerant coliforms. The stretching process reduced L. innocua contamination by more than 1 log CFU/g in the cheese curd. Therefore, it can be concluded that, in general, the microbial population is not significantly affected by the time-temperature combination used in the cheese stretching process (65 °C for 2 min). On the other hand, L. innocua showed sensitivity to the stretching process. Thus, low contamination levels in the cheese must be ensured by good milking practices combined with good manufacturing practices.
Quality of milk and effect of processing on the microbiological safety of Porungo cheese
Keywords: Queijo artesanal tradicional; Alimento seguro; Controle microbiano; Traditional artisanal cheese; Safe food; Microbial control; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA